Islamic Education Institutions and Sustainable Inclusive Education: Challenges and Prospects - Wardatul Karomah; Rahmat Hariyadi (Global Journal of Islamic Education, 2025)
This study aimed to analyze the future of Islamic Religious Education (IRE) institutions in realizing sustainable, inclusive, and Islamic value-based education. The focus was directed to how IRE institutions responded to global dynamics, social challenges, and the need for curriculum and educational management transformation in the modern era. Specifically, the study explored the strategic role of IRE in twenty-first-century education, while also identifying institutional obstacles, opportunities, and directions for reform. The method employed was library research with a descriptive qualitative approach, using scientific literature, reputable journals, academic books, and educational policy documents, which were analyzed through content analysis. The findings indicated that the future of IRE institutions largely depended on their ability to integrate principles of sustainable education, Islamic inclusivity, and adaptive governance. The novelty of this research lay in formulating an integrative and contextual conceptual framework for PAI institutions, making it relevant to twenty-first-century challenges. The results emphasized the urgency of institutional reform so that IRE could support equitable, participatory education rooted in the values of rahmatan lil ‘alamin.